Doświadczalne Badania Niektórych Własności Mechanicznych Gumy - Zahorski, S. (Engineering Transactions, 1962)
The paper contains a description of an experimental verification of the theoretical characteristics in the case of pseudo plate shear and simple tension, assuming that the material (rubber) is described by an elastic potential in a form constituting a generalization of the equation of M. Mooney (cf. [1]). Figs. 4,5 and 6 show the theoretical and experimental results for three rubber types: OKA - 1, OKB - 1, OKD - 1, the theoretical results being represented by the continuous curves. Good agreement is found in a relatively broad range of elastic strain. Making use of the theoretical relations and applying the method of least squares, the values of three material constants C1, C2 and C3 characterizing the mechanical properties of the rubbers tested (Table 4) are computed. The test results show also the correctness of the assumed deformation scheme and confirm the applicability of the M. Mooney equation in the range of strains not exceeding 30-40%.